2005
DOI: 10.1080/02844310510006349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgical or chemical delaying procedures on the survival of proximal pedicled venous island flaps: Am experimental study in rats

Abstract: To increase the survival of proximally pedicled venous island flaps, which are known to be safe only when small, we used surgical and chemical delaying procedures both individually and in combination for 7, 14, and 21 days. Survival was 1% in those flaps designated as controls, in which there was neither surgical nor chemical delay. However, it was 3%, 31%, and 68% at 7, 14, and 21 days, respectively, when surgical delay was used and 16%, 56%, and 86%, at 7, 14, and 21 days, respectively, when chemical delay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The total flap necrosis occurs in all AVF's, despite previous T-T micro-anastomosis. A high percentage of AVF's necrosis is similar to the results reported by other authors (Cho et al, 1998;Moshammer et al, 2003) and on pedicle vein flap on rats (Cutting et al, 1980;Daniel et al, 1990;Sano et al, 2003;Baser et al, 2005). CONCLUSION Non-conventional circulation in the flap is a relatively new and cheaper method in plastic and reconstructive surgery, that has been underestimated by many surgeons.…”
Section: Resultssupporting
confidence: 87%
“…The total flap necrosis occurs in all AVF's, despite previous T-T micro-anastomosis. A high percentage of AVF's necrosis is similar to the results reported by other authors (Cho et al, 1998;Moshammer et al, 2003) and on pedicle vein flap on rats (Cutting et al, 1980;Daniel et al, 1990;Sano et al, 2003;Baser et al, 2005). CONCLUSION Non-conventional circulation in the flap is a relatively new and cheaper method in plastic and reconstructive surgery, that has been underestimated by many surgeons.…”
Section: Resultssupporting
confidence: 87%
“…Total flap necrosis occurs in all AVF, despite the previous T-T micro anastomosis. A high percentage of AVF necrosis is similar to that reported in 1997 by Cho et al 20 , in 2003 by Morhammer et al 21 and in 2005 by Baser et al 22 , on pedicle venous flap on rats.…”
Section: Discussionsupporting
confidence: 80%
“…However, venous flaps are not as reliable as conventional flaps. If a reliable venous island flap is prepared, then various flaps can be designed on the surface of the body using the subcutaneous veins [4,5]. Yilmaz et al [6] showed on rabbit ears that the venous flaps were not as reliable as the conventional flaps, and a greater number of venous pedicles were associated with improved flap survival.…”
Section: Discussionmentioning
confidence: 99%